Moderate movement variability is optimal in massive practiced dart throws - Mahdi Nabavinik; Hamideh Abdolzadeh (IP Iermakov S.S., 2020)
Background and Study Aim. Movement variability is one of the fundamental topics concerning the control of human movement. In recent years, researches have focused on various aspects of variability, which has changed the noise to useful variable on human movement. Present study investigated movement variability level in high skilled dart players that repeated throws over many years. Material and Methods.  Seven experienced dart players (three women and four men) were threw 36 darts in three sets (each set 12 throws) from a standard distance (2.37 meters), while the kinematic features of the shoulder, elbow, and wrist were recorded during the throws. Qualisys motion capture system with six cameras was used to record the kinematics of the elbow. Results: entropy analysis revealed that greater variability in movement angle, velocity and acceleration resulted in better dart throwing performance but after reach to this level, throw variability was decreased. The remarkable point in these findings was that variability was constant across all samples despite the varied range of experience in throwing darts from 2.37 meters distance. Entropy analysis showed that in the throws of highly experienced individuals, variation led to greater throwing efficiency. Conclusions: these findings suggest that variability in a throwing activity, which revealed that moderate movement variability results in optimal throwing performance when dart throw has massive amount of practice during many years.